Manajemen Kanker Kolorektal - Agi Satria Putranto (MEDICINUS, 2022)
Colorectal cancer was infrequently diagnosed few decades ago, but the number of cases increased dramatically until it becomes the third most prevalent malignancy after breast and lung cancer. Population aging and on top of unhealthy lifestyle were major contributor to the significant rise of the disease. Management of colorectal cancer has markedly evolved, allowing improvement in terms of survival and advance in quality of life. Nevertheless, the rate of survival could be boosted by raising public awareness over colorectal cancer, education program that may lead to better health behaviour, as well as health system policy that support disesase screening, considering the characteristic of the disease that is often asymptomatic, particularly in the early development.